LABORATORY TESTS IN AESTHETIC PROCEDURES: THE RELEVANCE OF TESTS TO PREVENT COMPLICATIONS (REMUNOM, 2025)
This study analyzed the relevance of laboratory tests in aesthetic procedures, highlighting their role as an essential tool for preventing complications and consolidating Aesthetic Biomedicine as a scientific field. The main objective was to understand how laboratory screening contributes to clinical safety, result optimization, and the ethical valorization of professional practice. This is a bibliographic and qualitative research, developed through studies published in databases such as SciELO, PubMed, and Google Scholar. The analyses indicated that the absence of preliminary tests is associated with higher risks of infections, hematomas, necrosis, and adverse reactions, compromising both the patient’s integrity and the professional’s credibility. On the other hand, the incorporation of laboratory tests proved to promote the integration of aesthetics with other health fields, reinforcing the need for an interdisciplinary and holistic approach to the patient. Furthermore, despite regulatory advances, challenges remain regarding the lack of standardized protocols and the resistance of some professionals. It is concluded that laboratory tests should not be considered an optional step, but an ethical, scientific, and social duty, indispensable for the safe and responsible practice of Aesthetic Biomedicine.